Deciphering the ecology of the threatened microendemic species Euphorbia margalidiana - Llorens, Leonardo; Cortés, Lucas; Boira, Herminio (Frontiers in Plant Science, 2023)
Small islands play a critical role in the study of plant ecology and evolution. Here, we reveal the ecology of Euphorbia margalidiana, an endemic plant that thrives in a micro-island environment in the Western Mediterranean region. Through a detailed characterization of the habitat, including plant communities, microclimate, soil properties, and germination assays, we examine the effects of biotic and abiotic factors on the distribution of this endangered species. We also analyze its pollination biology, evaluate the success of vegetative propagation, and discuss its potential use in conservation strategies. Our results show that E. margalidiana is a characteristic species of the shrub ornitocoprophilous insular vegetation of the Western Mediterranean. The seeds have a very low dispersion capacity outside the islet and that seed-derived plants have higher survival rates under drought conditions than those vegetatively propagated. The main volatile compound emitted from the pseudanthia is phenol which attracts the plants' main and almost exclusive pollinators in the islet, flies. Our results confirm the relictual status of E. margalidiana and highlight the importance of key adaptive traits that enables the survival of this species in the harsh micro-island environment of Ses Margalides.